2022
DOI: 10.3390/ph15070777
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Anticancer Effects of Brominated Plastoquinone Analogs with Promising Cytotoxic Activity in MCF-7 Breast Cancer Cells via Cell Cycle Arrest and Oxidative Stress Induction

Abstract: Plastoquinone analogs are privileged structures among the known antiproliferative natural product-based compound families. Exploiting one of these analogs as a lead structure, we report the investigation of the brominated PQ analogs (BrPQ) in collaboration with the National Cancer Institute of Bethesda within the Developmental Therapeutics Program (DTP). These analogs exhibited growth inhibition in the micromolar range across leukemia, non-small cell lung cancer (EKVX, HOP-92, and NCI-H522), colon cancer (HCT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The versatility of quinone chemistry in drug development is extensive (Borba‐Santos et al, 2022; Di Marco et al, 2021; Dos Santos et al, 2022; Mahalapbutr et al, 2022). Our recent studies have demonstrated the in vitro and in silico anticancer activities of brominated PQ analogs against MCF7 breast cancer cells via cell cycle arrest and oxidative stress induction (Jannuzzi et al, 2022). This was followed by another report claiming the anticancer potential of chlorinated PQ analogs against the MCF7 cell line via oxidative stress, apoptosis, and the suppression of cell proliferation (Jannuzzi et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The versatility of quinone chemistry in drug development is extensive (Borba‐Santos et al, 2022; Di Marco et al, 2021; Dos Santos et al, 2022; Mahalapbutr et al, 2022). Our recent studies have demonstrated the in vitro and in silico anticancer activities of brominated PQ analogs against MCF7 breast cancer cells via cell cycle arrest and oxidative stress induction (Jannuzzi et al, 2022). This was followed by another report claiming the anticancer potential of chlorinated PQ analogs against the MCF7 cell line via oxidative stress, apoptosis, and the suppression of cell proliferation (Jannuzzi et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Reactions between 1,4‐quinones and amines that address biologically important lead molecules have been extensively reported (Lima et al, 2021; Lopez‐Lira et al, 2021; Pauli et al, 2023; Uysal et al, 2021; Varricchio et al, 2020; Yildirim et al, 2022). In line with these studies, we investigated halogenated (brominated and chlorinated) and non‐halogenated plastoquinone (PQ) analogs to understand their antiproliferative profiles against breast cancer cell lines (Jannuzzi et al, 2021, 2022; Yilmaz Goler et al, 2022). Earlier studies motivated us to use the quinolinequinone moiety as the main framework for our new molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations